A HIERARCH AND HIS AGE. THE LIFE AND THE ACTIVITY OF BISHOP VASILE MOGA (1774-1845) AS REFLECTED IN THE ROMANIAN HISTORIOGRAPHY - Mihai-Octavian Groza; Iuliu-Marius Morariu; Diana-Maria Dãian (Astra Salvensis, 2019)
The life and the activity of bishop Vasile Moga (1774-1845) were briefly analysed in the Romanian historiography both because of the absence of some systematic researches on the archivist material existing in Romania and abroad and also due to the rich activity developed by his successor, the bishop and afterwards archbishop and metropolitan Andrei, baron of Şaguna. His figure was analysed after his contribution to the development of the Romanian education, to the improvement of the moral-religious life of the eparchy, to the national-political fight of the Transylvanian Romanians and less after his contributions to the institutional realities, the organization of the bishopric, the relation with the archpriestships and the eparchies, constituting a lack of the historiography that remains to be solved. We will aim through our study, based on the analysis of the Romanian writings dedicated to the life and the activity of bishop Vasile Moga, at capturing the main phases and research directions as well as its significations hoping that this modest study will focus the attention of the historians and theologians in order to make this honest hierarch, unduly marginalized come into prominence. The historiographical passages referring to bishop Vasile Moga‟s life and activity demonstrated the fact that over time he was an ,,aggrieved” of the historical writing compared to his successor, Andrei Şaguna.